أثر برنامج تدريبي قائم على الفصول الافتراضية على إكساب مهارة الفهم القرائي لدى التلميذات ذوات صعوبات الفهم القرائي في سلطنة عمان - شيبانية، عزاء هلال حارب
This study aimed to identify the effectiveness of the training program that is based on the virtual classrooms and to impart the reading comprehension skill of the sixth grade female students with reading comprehension difficulties in Al Dakhiliyah Governorate in the Sultanate of Oman. Also, it aimed to identify the extent to which teachers of learning difficulties were prepared to use virtual classrooms in teaching sixth grade female students with learning difficulties. Also, it aims to identify the viewpoint of students with reading comprehension difficulties regarding using virtual classrooms to impart them with the skill of reading comprehension. The researcher adopted the descriptive and quasi-experimental method in the current study. The study tools included the pre and post test, the training program based on the virtual classroom, and the interview. These tools were applied to 14 female students with reading comprehension difficulties in the sixth grade in Al Dakhiliyah Governorate in the Sultanate of Oman. The questionnaire was also applied to 159 teachers out of the Handling Learning Difficulties teachers in the Sultanate of Oman, and the study tools were also treated with statistical methods for each performance. The study found that there were statistically significant differences when teaching students the reading comprehension skill using the virtual classroom (Google Classroom) between the pre and post measurement at a significance level of 0.05 in favor of the post measurement. It also reached an agreement of the views of the Handling Learning Difficulties teachers on the use of virtual classrooms in teaching students with learning difficulties, with the presence of some obstacles that limit this use. In addition, it found that the sixth graders with reading comprehension preferred to receive lessons using the virtual classroom, as it helped and encouraged them to learn in an interesting and enjoyable way, and it also increased their motivation towards the learning process. However, the weak network connection and the large number of technical malfunctions in devices were among the obstacles that the students faced when using this type of classroom. Therefore, the researcher recommended the necessity to use this type of classes, and to reduce the obstacles that hinder the use of these classes. The researcher also suggested to carry out similar studies to this study that include different samples of students with learning difficulties to address different aspects that these students suffer from.